Revisiting groundwater chemical processes in a rapidly urbanizing basin - J. A. Torres-Martínez; B. Dorjderem; Jürgen Mahlknecht (Energy Reports, 2020)
Monterrey procures about 40% of its water supply from groundwater resources, considering several aquifers below and nearby. This city meets semiarid climate conditions with highly variable precipitation rates. The increasing demand for groundwater during drought conditions can deteriorate water quality, raising the energy consumption and costs of lifting, moving, distributing, and treating water. Thus, the major ion content of this resource was assessed, analyzing changes across the Monterrey Basin during the last 11 years to obtain a more robust geochemical concept of the study area. Waters from three wellfields (Buenos Aires, Santiago, Mina) with low mineralization were classified as recharge waters. Waters circulating across evaporite-silicate-carbonate sediments of the Monterrey Basin with gradually increasing salinity were classified as transition zone waters (Metropolitan area) and discharge zone waters (north and northeast of the city). According to this, it can be concluded that groundwater from the different Monterrey sources exhibits high-quality mineralized water, considering the analyzed parameters. Nevertheless, further attention must be paid on nitrate and sulfate occurrence and evolution in the transition and discharge zones.
Keywords: 330; Groundwater chemistry; Mexico; Monterrey; Urban aquifer